Indonesia Kepemimpinan Kepala Sekolah yang Efektif - Azizah, Wafiq Wafiq (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
The principal is one of the key factors in determining the realization of quality education. The principal functions as the manager and educational leader of the school institution. Effective management and leadership requires principals who are aware of modeling and exhibit characteristics such as ideal influence, inspiration, motivation, intellectual stimulation and individual consideration. They must employ teaching staff, work within clear time frames, establish interpersonal relationships, develop principles of fair and accountable accountability, and be able to work in teams. The principal is one of the key and important factors in creating an effective school. Effective school principals: a) have a strong vision of the future of their school, b) have high expectations, c) ensure that learning runs effectively. d) efficient use of time and minimize negative stress and conflict. e) utilizing various learning resources, f) utilizing information to direct learning planning. g) carry out evaluations and repairs irrationally. Keywords: Leadership, Super vision, Managerial